(untitled) (PJDOL, 2023)
The objectives of this study were: to analyze the academic, social, physical and moral impact of internet utilization on university students and to give recommendations to improve the situations and for further research. This was a survey type descriptive research. Population of the study comprised of all the students enrolled in BS programs in the eight randomly selected universities of Khyber Pakhtunkhwa Pakistan. Seven hundred BS students were sampled from the selected universities using purposive sampling method.